Mejoramiento genético y actividades relacionadas. Actividades relacionadas. Africa. Africa del Sur - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
The Southern Africa Development Coordination Conference (SADCC) region covers Tanzania, Malawi, Zambia, Zimbabwe, Mozambique, Angola, Botswana, Lesotho, and Swaziland, and is the largest of the 3 regions hosting a CIAT bean program in Africa. Bean production from the SADCC region amounts to about 564 thousand t of dry seed, which is approx. a quarter of the total production of Africa. The strength of national programs differs substantially across the 9 countries. The Tanzania program is the largest. In most other countries in southern Africa, national scientists are part of grain legume research teams not devoted solely to beans. CIAT's regional activities have included the conduct of the 1st steering committee meeting, the convening of a bean fly workshop in Arusha, Tanzania, and the attendance of a board meeting of Southern African Center for Cooperation in Agricultural Research in Lusaka, Zambia. (CIAT)